Faktor Penyebab Kekosongan Keterwakilan Perempuan dalam Formasi DPRD Kabupaten Lembata Periode 2019-2024 - Natalia Ina Barek L. Wuyo; Yuli Setyowati (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The representation of women in the Legislature is a must in democracy, but the 2019 Lembata Regency legislative elections brought defeat to all female candidates resulting in a vacancy for women's representation to sit in the building“Peten Ina”. Reports from the General Election Commission explained that all political parties participating in the election had complied with the affirmation policy as contained in Law Number 7 of 2017 concerning Elections and Law Number 2 of 2011 concerning Political Parties, but descriptive representation has yet to materialize. Whereas the representation of women in the legislature is very important in order to be able to bring women's issues into decision-making that has a broad impact on society. This study aims to describe the factors causing the vacancy of women's representation in the Lembata Regency legislature. This study used a qualitative descriptive research method, and the data collection techniques used were interviews, observation and documentation. The results showed that there were 5 factors that caused the vacancy of women's representation in the legislature, namely the lack of goodwill from political parties in an effort to increase women's representation as evidenced by the ineffectiveness of party recruitment and regeneration patterns; the patriarchal paradigm is still rooted; limited funding from female candidates; lack of caleg capacity which has an impact on the lack of a political strategy for female candidates. So that departing from the vacancy of women's representation shows that political institutions have not been friendly to women.